Choreographing in nomadic traces - von Bagh, Jenni-Elina (My University, 2018)
This written part of my final theses work focuses on my own choreographic work through a nomadic framing. I go through methodologies and principles in choreographing, that bring us closer to a question of non-identification, pre-individuality and nomadism. I am curious to consider the phase of my artistry as a transitional phase concerning my personal relationship to dance and choreographing but also considering a general atmosphere in philosophical discourses and art; a step from postmodern and poststructuralist discourses to the realm of new materialism and posthumanism. Through my writing and exemplification of my own artistic works, especially my artistic final work: a life -nomadic melodrama, I want to analyze how a co-resonance of specifically Gilles Deleuze’s philosophy influence and give support to artistic work and artistic thinking. In the first chapter I go through couple of general aspects in my choreographic working. I articulate three different perspectives that can be generalized as artistically valuable. These are such as translation as a choreographic method, semantic and somatic as compositional co-partners, and the question of body in the realm of becoming. In the second chapter I introduce theoretical backgrounds to my artistic working through philosophic concepts such as ”becoming”, ”assemblage”, ”nomadism” and ”a life” that specifically resonated in the way I approach my artistic work as non-essentialist. The third chapter is an investigation of my artistic final work a life -nomadic melodrama. First I elaborate some theoretical and artistic influences for the starting point of the process. Then I introduce some methodologies used in the process. I will also introduce the structure of the piece to exemplify how the before mentioned concepts concretize in this particular work. In the fourth chapter I go through certain nomadic principles that has affected especially the artistic process of a life - nomadic melodrama and my artistic thinking in general.
Keywords: assemblage; new materialism; posthumanism; a life; body; Nomadism.; Becoming (Philosophy); Posthumanities.; Transformation.; Choreography.; koreografia; tanssiteokset; paimentolaisuus; posthumanismi; materialismi; ruumiillisuus; filosofia; koreografi; dansverk; nomadism; posthumanism; materialism; kroppslighet; filosofi; fi=koreografia|sv=koreografi|en=Choreography|